Designing of Lighting Automation System Based on Arduino Bluetooth Interface using Android Smartphone as Platform - Morallo, Narcisa (JPAIR Multidisciplinary Research, 2017)
Bluetooth is now mainstream that it has become synonymous with the 21st century. The wireless technology allows exchanging data over short distance using short wavelength radio transmission, providing convenience, intelligence and controllability. In this paper, a home lighting control system using arduino bluetooth interface with android smartphone as platform is proposed and prototyped. Technology in arduino, android smartphone and bluetooth are reviewed. HC-05 bluetooth SPP (Serial Port Protocol) module, designed for transparent wireless serial connection setup is being used in the design. Android application is downloaded to android smartphone to monitor and control the operation of the lighting system remotely. The application facilitates in controlling the operating pins of Arduino. Design shows that arduino bluetooth interfacing can control a house lighting using an android smartphone as a platform. In future lighting home automation, timer will be included to be more energy- efficient and highly scalable. For secured, ubiquitously accessible and remotely controlled lighting system, GSM module will be incorporated in future designs. It would be extended to the large-scale environment such as colleges, offices and factories, among others.